CROPS VARIETIES UNDER CONSERVATION: STUDY CASE CULTIVATED TRITICUM SSP. - Maria-Mihaela ANTOFIE; Camelia SAND SAVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The dynamic of crops domestication and use of edible wild plant species is well documented worldwide. The diversity of plant species used for food, changed during humankind history and lot of researchers pointed out the danger of species erosion that may negatively impact food security. The trade of crops is regulated at the international level and as a secondary effect is the promotion of new breed varieties. Today the scientific community is talking about neglected species and old varieties not eligible for trade and consequently removed from the today diet without taking into consideration the fact that their presence in the same agro-ecosystem for more than 50 years, increases their capacity to adapt to climate change effects. Therefore, huge efforts should be done to re-assessing our conservation strategies for breeding crops. At the European level it is already recognized the term “varieties under conservation”, that allows members states to maintain old varieties and landraces under specific conditions. The scope of this article is to evaluate the official status of conservation of Triticum ssp. in our country by taking into account the history of cultivation and breeding programmes. At least 6 edible fossilized wheat species were found in human settlements for more than 6,000 years (i.e.: T. aestivum, T. dicoccoides, T. dicoccum, T. durum, T. monococcum and T. spelta). If einkorn and emmer wheat were common between Neolithic and Middle Age, today they are almost absent. Only six varieties of bread wheat are today officially recognized as “varieties under conservation”, a series of more than 50 old varieties breed after 1927 being not yet officially recorded.